The Effectiveness of Cucurbitacin B in BRCA1 Defective Breast Cancer Cells - Promkan, Moltira (Public Library of Science, 2013)
Cucurbitacin B (CuB) is one of the potential agents for long term anticancer chemoprevention. Cumulative evidences has shown that cucurbitacin B provides potent cellular biological activities such as hepatoprotective, anti-inflammatory and antimicrobial effects, but the precise mechanism of this agent is not clearly understood. We examine the biological effects on cancer cells of cucurbitacin B extracted from a Thai herb, Trichosanthes cucumerina L. The wild type (wt) BRCA1, mutant BRCA1, BRCA1 knocked-down and BRCA1 overexpressed breast cancer cells were treated with the cucurbitacin B and determined for the inhibitory effects on the cell proliferation, migration, invasion, anchorage-independent growth. The gene expressions in the treated cells were analyzed for p21/(Waf1), p27(Kip1) and survivin. Our previous study revealed that loss of BRCA1 expression leads to an increase in survivin expression, which is responsible for a reduction in sensitivity to paclitaxel. In this work, we showed that cucurbitacin B obviously inhibited knocked-down and mutant BRCA1 breast cancer cells rather than the wild type BRCA1 breast cancer cells in regards to the cellular proliferation, migration, invasion and anchorage-independent growth. Furthermore, forcing the cells to overexpress wild type BRCA1 significantly reduced effectiveness of cucurbitacin B on growth inhibition of the endogenous mutant BRCA1 cells. Interestingly, cucurbitacin B promotes the expression of p21/(Waf1) and p27(Kip1) but inhibit the expression of survivin. We suggest that survivin could be an important target of cucurbitacin B in BRCA1 defective breast cancer cells.